A fully-coupled dynamic model for the fundamental shear horizontal wave generation in a PZT activated SHM system. (1st February 2019) - Li, Peng; Shan, Shengbo; Wen, Fuzhen; Cheng, Li
Highlights: A theoretical model on the shear horizontal wave generation is established. The correctness is proved via FEM and experimental results. A truncation criterion related to wavelength and excited frequency is proposed. The effect of dynamic coupling between the PZT and the plate is revealed. Abstract: The fundamental shear horizontal (SH0) wave in plate-like structures is of great importance in structural health monitoring (SHM) applications due to its unique non-dispersive nature. Its generation or reception using piezoelectric (PZT) wafers, however, is always a critical and challenging issue. In this study, a theoretical model on the shear horizontal (SH) wave generation is established based on the continuum mechanics theory. The model considers the dynamic properties of a PZT actuator and its coupling with a host plate through a bonding layer, whose mechanical property is modelled by considering a continuous shear stress but different tangential displacements across the adhesive layer. Closed form solutions are obtained using the trigonometric series decomposition and the modal superposition method. The solution series are shown to exhibit fast convergence. The model, along with some typical physical phenomena, is validated through comparisons with the FEM and experimental results. Numerical analyses allow establishing a series truncation criterion, in relation to the size of the actuator and the wavelength of the SH0 wave. It is shown that the dynamic coupling between the PZT and the plate should be considered in the design of PZT-activated SH0 wave generation. Typical phenomena in different frequency regions and their impact on the SH0 wave generation are scrutinized and discussed. The proposed theoretical model is expected to provide a useful tool for the physical mechanism exploration, structural design and eventually system optimization for SH0 wave generation in SHM applications.